E-CRM Mobile Applications To Improve Customer Loyalty (Case Study: PT Supermal Karawaci) - Padeli, Padeli; Mulyati, Mulyati; Faisal, Muhammad; Debora, Siska (Pandawan, 2020)
Disruptive Technology is one of the backbones of Indutry4.0, In this era the company's large size is no longer a guarantee. Speed ​​in adapting to the development and behavior of consumers is the main key. Therefore, companies must be sensitive and do self-introspection so they can detect their position in the midst of the development of science and technology in order to maintain their existence and have the opportunity to dominate the market. PT Supermall Karawaci, which is engaged in the retail business, needs to adapt and understand this rapid technological development, so for this business sector requires interaction with customers. The current system is good, but in some procedures that make customer service less than optimal and will be better if there is an effort so that customer loyalty can increase and of course the company's profit will increase. Therefore, the writers make this problem as a foundation in research and application development (E-CRM), the writers use the method of observation, elicitation, SWOT, Unified Modeling Language (UML), prototype and black box as methods of data collection, analysis, design and testing. For design, programming, web server and database, the writer uses Adobe XD applications, Android Studio, PHP, XAMPP and Microsoft SQL Server.